Rattus tanezumi - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
661. Oriental House Rat Rattus tanezumi French: Rat tanezumi / German: Asiatische Hausratte / Spanish: Rata caseraoriental Other common names: Oriental Rat, Oriental Roof Rat, Tanizumi Rat Taxonomy. Mus tanezumi Temminck, 1844, “japonais est Ta-nezumi.” Interpret- ed by J. K. Jones, Jr. and D. H. Johnson in 1965 as “Japan . vicinity of Nagasaki on the southern island of Kyushu.” Taxonomy of R. tanezum: and the entire R. rattus species complex (R. rattus and its relatives) is in flux, with possibly 4-6 distinct species in the R. rattus complex. As outlined under R. rattus, there are six main lineages within the R. rattus clade and four distinct species: R. rattus (Lineage I, 2n = 38), R. tanezumi (Lineage II, III and IV, 2n = 42 and 2n = 40 in Sri Lankan Lineage IV), R.sakeratensis (Lineage V), and R. tiomanicus (Lineage VI). Lineage II is the most widespread, probably originating in northern and western South-east Asia and southern China, Hainan, and Taiwan, spreading throughout China, Japan (including Ryukyu Islands), and various parts of Indonesia, Philippines, and Melanesia. Lineage III probably originated in northern parts of the Indian Subcontinent, being found in modern times only surrounding Himalayan region, including north-eastern Afghanistan, northern Pakistan, northern India, south-western China, Nepal, and Bhutan. Lineage IV, which is the most geographically complex lineage, probably originated in southern South-east Asia, spreading currently throughout Indonesia and Philippines, although its present in Sumatra, Borneo, and many small islands is uncertain. Lineage IV is also found in Sri Lanka, probably coming from Java or mainland south-eastern Asia. As currently understood genetically, Lineage 1 is sister to Lineage II, both of which are sister to Lineage III. The clade containing Lineages I-III are sister to a clade including Lineage IV-VI, and Lineage IV and V are sister to one another, with Lineage VI assister to them both. This phylogeny leaves R. tanezumi paraphyletic. It probably will be ...